Exterior strengthening for ASR damaged concrete: A comparative study of carbon and basalt FRP. (28th February 2020) - Diab, S.H.; Soliman, A.M.; Nokken, M.
Highlights: The degree of ASR expansion at the strengthening time is critical. Fiber reinforcement polymer is an adequate strengthening material for ASR. The earlier strengthening, the better the performance of strengthened elements. BFRP is a strong competitor for CFRP at a lower cost. Abstract: Recently, many composite materials have been used to strengthen and extend the service life for deteriorated concrete; particularly in the case of alkali-silica expansion (ASR). This study compares the effectiveness of carbon fiber reinforcement polymer (CFRP) and basalt fiber reinforcement polymer (BFRP) as strengthening materials for ASR-damaged concrete. Sensitivity for strengthening time and corresponding residual properties, including expansion, compressive strength, modulus of elasticity, Poisson's ratio, and stiffness damage index were evaluated on specimens strengthened by both materials. Results reveal that the degree of expansion at the strengthening time has a higher impact on the performance of strengthened structures than that of the used strengthening materials properties. Early application of CFRP and BFRP reveal 32% and 27% reduction in expansion, respectively. The same performance of concrete specimens can be maintained through the proper selection of the strengthening materials and strengthening time. It is anticipated that these results pave the way for wider implementations for various types of fiber reinforcement polymer in strengthening applications.